Organic Challenges to Constitutional Justice in Iraq: Analytical Study - صباح عبدالرحمن شالاو; ملا عزيز سردار (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study examines the organizational challenges that face the Iraqi Constitutional Court in realizing constitutional justice through addressing the major weaknesses and shortcomings that exist in the constitutional and legal organization of the Federal Supreme Court along with its negative effect on the existence and required organizational independence of the Court from the other public authorities and its constitutional role in guaranteeing constitutional justice or the constitutional goals that the court has been establishment for by exercising its competences, enforcing the provisions of the Constitution and protecting it from being violated by the public authorities. The article argues that the organizational independence of the Federal Supreme Court from the other authorities ensures that the Court carries out the constitutional tasks entrusted to it in the best manner and in accordance with the constitutional provisions and the requirements of constitutional justice